(untitled) (Bangladesh Critical Care Journal, 2022)
Background: The majority of patients admitted to the hospital for elective surgery experience anxiety preoperatively which can adversely influence the surgical procedure as well as the patient’s recovery. Reduction of anxiety and fear at the preoperative period in patients of elective surgery is essential for surgical preparation. Benzodiazepines are the most commonly used drugs for this purpose. Materials and Methods: The study was carried out on a series of 60 consecutivepatients, aged 18-60 years, admitted for elective surgery under General Anaesthesia, in Combined Military Hospital, Chattogram during the period September 2021 to February 2022. Patients receiving bromazepam or lorazepam as preoperative medication were selected. Anxiety was scored using VAS (Visual Analogue Scale), sedation was scored by using the Ramsay Sedation scale and anterograde amnesia by asking about preoperative events after 24 hours of premedication. Results: While evaluating mean anxiety reduction only, mean reduction is greater in the lorazepam group compared to that of bromazepam. Sedation level was less achieved with bromazepam. In the lorazepam group, a greater number of patients could not recall preoperative events but incidence of adverse effects was significantly more in this group. Conclusion: The standard administration of bromazepam before the procedure provides patients with a moderate reduction of periprocedural anxiety. Premedication of lorazepam is associated with a high incidence of adverse effects. Therefore, this study does not support the routine use of lorazepam as premedication to reduce anxiety before surgery. Bangladesh Crit Care J September 2022; 10(2): 110-115